2016
DOI: 10.3389/fpls.2016.01546
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Signaling Regulates Synchronised Growth of Symbiotic Epichloë Fungi with the Host Grass Lolium perenne

Abstract: The seed-transmitted fungal symbiont, Epichloë festucae, colonizes grasses by infecting host tissues as they form on the shoot apical meristem (SAM) of the seedling. How this fungus accommodates the complexities of plant development to successfully colonize the leaves and inflorescences is unclear. Since adenosine 3′, 5′-cyclic monophosphate (cAMP)-dependent signaling is often essential for host colonization by fungal pathogens, we disrupted the cAMP cascade by insertional mutagenesis of the E. festucae adenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 85 publications
2
11
0
Order By: Relevance
“…Indeed, all fusion‐negative E. festucae strains obtained to date have a stunted host phenotype (Scott, Green, & Berry, ). However, given E. festucae mutants in cAMP/PKA signaling (Voisey et al, ), apoplastic iron homestasis (Johnson et al, ), and chromatin regulation (Chujo et al, ), exhibit a proliferative growth phenotype in planta but are not defective in cell fusion, an alternative more general hypothesis is needed to explain these results. One possibility is alkalinization of the apoplast (Scott et al, ); a change that activates signaling through the PacC‐mediated pH responsive and MAP kinase pathways, triggering invasive growth (Fernandes, Segorbe, Prusky, & Pietro, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all fusion‐negative E. festucae strains obtained to date have a stunted host phenotype (Scott, Green, & Berry, ). However, given E. festucae mutants in cAMP/PKA signaling (Voisey et al, ), apoplastic iron homestasis (Johnson et al, ), and chromatin regulation (Chujo et al, ), exhibit a proliferative growth phenotype in planta but are not defective in cell fusion, an alternative more general hypothesis is needed to explain these results. One possibility is alkalinization of the apoplast (Scott et al, ); a change that activates signaling through the PacC‐mediated pH responsive and MAP kinase pathways, triggering invasive growth (Fernandes, Segorbe, Prusky, & Pietro, ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of both forward and reverse genetics studies in Epichloë festucae have identified key signaling pathways for the symbiotic interaction with the grass host, Lolium perenne. These include fungal cell wall integrity [36,37], pheromone response/invasive growth [38], and stress-activated [39] mitogen-activated protein kinase (MAPK) pathways, cAMP [40], calcineurin [29], pH [31], light [41,42], reactive oxygen species (ROS) [43][44][45] and lipid [46] signalling pathways. These genetic analyses uncovered host interaction phenotypes ranging from a mild alteration in the host tiller morphology to severe stunting of tiller growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although ROS play a major role in regulating E. festucae growth in planta , the NoxA and NoxB complexes are not the only signalling pathways required for controlling the establishment and maintenance of a mutualistic symbiotic association (Scott et al , ). A siderophore for maintaining iron homeostasis (Johnson et al , ), the transcription factor ProA (Green et al , ; Tanaka et al , ), the stress‐activated and cell wall integrity mitogen‐activated protein kinase (MAPK) signalling pathways (Becker et al , ; Eaton et al , ), the STRIPAK complex (Green et al , ), cAMP/PKA (Voisey et al , ) and calcineurin (Mitic et al , ) are all required for maintaining the symbiosis and cause similar host‐association defects when disrupted. Given the similarities between mutant phenotypes, the molecular mechanisms which facilitate gene regulation and cross talk between the Nox complex components and the different signalling pathways in E. festucae –host associations are of considerable interest and still relatively poorly described.…”
Section: Discussionmentioning
confidence: 99%